Current Topics in Tropical Emerging Diseases and Travel Medicine 2018
DOI: 10.5772/intechopen.79984
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy: The Ancient and Stubborn Disease

Abstract: Leprosy can be caused by an infection of Mycobacterium leprae commonly acquired through contact with an infected person. Clinical presentation depends on the patient's immune status at the time of infection and during the course of disease. Leprosy is associated with disability and marginalization. The Global Leprosy Strategy 2016-2020 released in April 2016 underscored its goal of "accelerating towards a leprosy free-world." Today's leprosy differs from the leprosy of the past, but yet there are still many th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Economic growth that continues to increase does not guarantee a reduction in the level of income inequality in a country. Based on a survey conducted by the International NGO Forum of Indonesia (INFID) it was reported that the richest 1% of people in Indonesia control 49.3% of national wealth, and even the richest 10% control 75.7% of national wealth (Mawardi, 2018). In developing countries, the main focus of economic development is still based on increasing economic growth alone, causing exploitation of natural resources and causing CO2 emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Economic growth that continues to increase does not guarantee a reduction in the level of income inequality in a country. Based on a survey conducted by the International NGO Forum of Indonesia (INFID) it was reported that the richest 1% of people in Indonesia control 49.3% of national wealth, and even the richest 10% control 75.7% of national wealth (Mawardi, 2018). In developing countries, the main focus of economic development is still based on increasing economic growth alone, causing exploitation of natural resources and causing CO2 emissions.…”
Section: Introductionmentioning
confidence: 99%